Kuepferia kanchii sp. nov. (Gentianaceae) from Sikkim Himalaya. (29th March 2016) - Maity, D.; Dey, S. K.; Favre, A.
Abstract : Kuepferia kanchii D. Maity, Sentu K. Dey & Adr. Favre, a new species from Sikkim Himalaya, is described and illustrated. It differs from its close relative K. infelix (C. B. Clarke) Adr. Favre ( = Gentiana infelix C. B. Clarke) by having sessile and smaller flowers, and smaller floral parts. Kuepferia kanchii is further characterized by a white corolla with bluish green patches on the outside at the base of each corolla lobe, and a corolla tube flushed with light green inside towards the base, blue filaments, sessile stigma, smaller capsule, and trigonous–elongated, ca 0.8 mm long and curved seeds.